Respon Siswa Terhadap Media Canva Dalam Kegiatan Menulis Teks Pidato Persuasif Pada Siswa Kelas IX MTS Al-Farisy - Fajar Nurfadillah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research was motivated by students' difficulties in writing persuasive speech texts, based on observation results. The aim of this research is to determine students' responses to learning to write persuasive speech texts using Canva media for class IX students at MTs Al-Farisy. The research method used is descriptive qualitative with an instrument in the form of a questionnaire. The research results show that the application of Canva media in learning to write persuasive speech texts that was carried out in this research found an average gain of 82.65% in the